The social, intercultural and personal conditioning factors that interfere with inclusive education in times of covid-19 - Hernández Fernández, Antonio (2022)
The general objective of this work is to analyze the relationship between inclusive education and the social, intercultural and personal conditions of teachers in times of pandemic (COVID-19) through structural equation methodology. This methodology contributes to the research objective by being able to relate the study dimensions in a mathematical way. The sample, selected by convenience (Spain-Ecuador), is made up of 810 university teachers. The conclusion is that the highest relationship is between the dimensions intercultural condition and personal condition, while the lowest relationship is between intercultural condition and social condition. Inclusive education, therefore, is mediated by these conditioning factors and, in spite of COVID-19, it is manifested at the moment of sharing with people from other cultures, with empathy in difficult situations of pandemic.